معوقات الاستثمار في اليمن والسياسات المقترحة لتوفير بيئة استثمارية محفزة - المكردي محمد علي (Journal of Amran University, 2023)
This study aimed to analyze the investment environment in Yemen. It explored the investment obstacles and the most important reforms that have been adopted and implemented by previous governments in order to provide an attractive investment environment. The study also examined the current situation for investment in Yemen and identified the most important obstacles that investment suffers from. The study used a descriptive analytical approach and found that the investment environment in Yemen continued to suffer from severe weaknesses in many aspects. This negatively affected the volume of national investment, despite the availability of some stimulating elements for investment in Yemen and the efforts made by successive Yemeni governments to provide an environment conducive to investment. The study concluded that the Yemeni government needs to formulate an investment policy that helps to encourage national investors and provides the appropriate environment for foreign investors. This will enhance the flow of foreign investment, due to the availability of natural resources in Yemen that have not yet been exploited. In addition, the availability of active and qualified human beings will enhance the role of investment in the process of growth and economic development in Yemen.